Enhancing the effectiveness of the Islamic microfinance programme: experience of Lembaga Zakat Selangor - Hamdan, Hamdino; Othman, Pazim @ Fadzim; Wan Hussin, Wan Sabri (Kolej Universiti Poly-Tech MARA, 2015)
Many experiences around the globe showed that Islamic Microfinance Programs (IMP) based on Shariah and Islamic finance concept, have become more significant in creating new job opportunities and generating income for the purpose of increasing social and economic status of the poor and alleviating poverty. The integration of entrepreneurial concept, training and microenterprise into IMP also contributes in increasing the effectiveness of the programme. ‘Asnaf Entrepreneurs Development Programme’ (AEDP) conducted by Lembaga Zakat Selangor (LZS) is among the pioneers and most established IMP in Malaysia. The implementation of IMP, which was preceded by selection process of asnaf participant and also accompanied by training and good monitoring, is effective in developing asnaf entrepreneur and improving poor asnaf income. Asnaf entrepreneurs’ development requires not only provision of financing in an interest free-based system but it also needs the provision of other services. The purpose of this paper is to suggest a way to improve the effectiveness of IMP in Selangor. The approach used to measure and evaluate the effectiveness of the IMP in Selangor is based on changes in revenue levels shown by the participants of the program among the poor asnaf and then develop a concept based on the literature review, research findings and comparison with the most successful microfinance programs in Malaysia, namely Amanah Ikhtiar Malaysia (AIM). This paper shows how in the Islamic perspective, spiritual development is necessary in improving the effectiveness of IMP in Selangor.